EVALUATION WORK PLAN IMPLEMENTATION DEPARTMENT OF LABOR KARIMUN 2014 - Sonia Selviana; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Work Plan Department of Labor is a technical document which is the operational guidelines for the preparation of annual work program for the current year. While the function is as a guide in the management of the work to be more focused activities in accordance with the vision and mission of the District Government on the implementation of the Work Plan Karimun. Department of Labor Karimun is lack of budget for training, is not yet optimal for the protection of labor and the lack of infrastructure the Department of Labor Karimun. Objective: 1) To study and analyze how the implementation of the work plan on the Department of Labor Karimun 2) To determine the factors that affect the implementation of the work plan of the Department of Labor Karimun. Theoretical concepts using Nurcholis (2003) as a guideline research Implementation Evaluation 1) Input is the input required for the implementation of the policy, 2) process that is the policy formulated in the form of direct services, 3) The output is the result of the implementation of policies and 4) Outcomes ie an executor policies have a significant impact on the target group. The informants were taken from some employees Department of Labor Karimun. Population serve as informants for this study using qualitative research. The types and sources of data used primary data, ie data obtained directly from the respondents and secondary data, ie data obtained through reporting, books and records. Data collection technique used interview, observation, documentation. Data analysis techniques by means of data collection, data reduction, data presentation, and draw conclusions. From the results obtained in the research work plan implementation Department of Labor Karimun how big objectives of the work plan can already covered or illustrated clearly that the implementation of this Renja still many obstacles or not everything went smoothly. At the Department of Labor Karimun impact on manpower development process, efforts to improve labor skills against free competition-based economy will be difficult to achieve and to create reciprocal government and society will be difficult to be realized. Factors that affect the implementation of the work plan delays the Department of Labor in 2014 Karimun Regency is located in Dana, Infrastructure, Communications and Resources. Thus concluded the evaluation of the Department of Labor Karimun is optimal in the quality of execution for the evaluation aims to determine the quality of the implementation of the run, Keywords: Evaluation, Work Plan, Program, Department of Labor